Answer:
[tex]y = - 3x + 5[/tex]
You should also try solving it yourself to make sure I did not make any mistake.
Step-by-step explanation:
Equation
[tex]y = mx + b[/tex]
First we need to know the slope
[tex]slope = \frac{y1 - y2}{x1 - x2} [/tex]
[tex]slope = \frac{2 - ( - 1)}{1 - 2} = \frac{3}{ - 1} = - 3[/tex]
So far the equation will look like this
[tex]y = - 3x + b[/tex]
To get the b you insert a point into the equation like this. I picked point (1,2)
[tex]2 = - 3 \times 1 + b[/tex]
[tex]b = 5[/tex]
We could also check it with the other point and see if we get the same answer.
[tex] - 1 = - 3 \times 2 + b[/tex]
[tex]b = 5[/tex]
So the equation is
[tex]y = - 3x + 5[/tex]